Organochlorine and pyrethroid residue in fish and sediment of Lake Singkarak, a tropical deep lake - Ibrahim, Aiman; Muhamad Suhaemi Syawal; Asep Nugraha Ardiwinata; Sugiarti; Mohamad Awaludin Adam; Wathri Fitrada; Riky Kurniawan (BRIN Publishing, 2023)
Agricultural activities still involve the use of synthetic pesticides to support the increase of their products. On the other hand, the use of synthetic pesticides such as organochlorines and pyrethroids may contribute to the decline of aquatic ecosystem health due to the accumulation of their residues in sediments and organisms. The current study aimed to assess the levels of organochlorine and pyrethroids pesticide residue in endemic fish and sediment from Lake Singkarak. Bilih fish and sediment samples were taken in June 2021 at ten (10) sampling sites in Lake Singkarak. The samples were extracted and analyzed by gas chromatography. Seven organochlorine compounds were measured, including aldrin, endrin, dieldrin, DDT, heptachlor, lindan, and endosulfan. Meanwhile, three compounds chosen from the pyrethroid group, cypermethrin, permethrin, and α-cypermethrin, were also measured. Four organochlorine compounds, aldrin, dieldrin, DDT, and endrin, were detected in bilih fish in three different sites. Dieldrin had the highest concentration at nd-0.007 mg/kg, followed by DDT, endrin, and aldrin. Meanwhile, in the sediments, no organochlorine compounds were detected from all observed sites. Pyrethroid compounds were detected in bilih fish at six sites. The compound with the highest concentration was permethrin (nd-0.02 mg/kg), followed by cypermethrin and α-cypermethrin. The surface sediment from three sites contained two pyrethroid residues, permethrin and α-cypermethrin, at nd-0.002 and nd-0.001 mg/kg, respectively. Our findings show that the residual levels of organochlorine and pyrethroid in bilih fish still meet the standards set by the Codex Alimentarius Commission (CAC). Nevertheless, Bilih fish accumulate more pesticide than surface sediment, so it is essential to be aware of their potential accumulation in the human body as the final consumer. Restriction on synthetic pesticide application is necessary to reduce its residue input into the lake waters for ecological and human health.